Does teaching writing through Canva application assist students’ writing performance? - Amanda, Maudiya Dwi; Megawati, Fika; Mandarani, Vidya (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study involves the issues of teaching writing in English skills in junior high school in the context of the digital world, highlighting the need to utilize technology-driven tools. Canva, an effective design tool, is included in the study as a possible alternative for improving students writing skills. The study aims at looking into the impact of utilizing Canva on students' writing skills and their assessment of the application's contribution to writing creativity. The report examines six connected research that illustrates Canva’s beneficial effects on several aspects of learning and teaching. A mixed-method approach is used in the methodology, employing a randomized pre-test-post-test control group design. Thirty-eight eighth-grade SMP Negeri 2 Sukodono students participated in the study. To examine Canva's effectiveness in developing writing skills, quantitative data obtained through pretest and posttests is analyzed using the Wilcoxon test. Furthermore, data from a questionnaire are used to investigate students’ impressions of Canva’s usefulness, ease of use, and suitability for supporting writing abilities. The results show significant improvements in the experimental group, validating that Canva improves students’ writing skills positively. The results of the questionnaire show that students have a high level of acceptance and good impressions of Canvas's utility, ease of usage, and suitability for improving writing skills. The findings add to the expanding research proving Canva's effectiveness as an English language learning tool. The report encourages additional research to investigate Canva’s long-term impact in various learning contexts and deployment methodologies.